Clinical applications of MRI in assessing musculoskeletal diseases and injuries - Pratap Dhimar, Chandra; Vaishnaw, Aayush (Journal of Neonatal Surgery, 2025)
Magnetic Resonance Imaging (MRI) has become an essential diagnostic tool in clinical settings, especially for assessing musculoskeletal diseases and injuries. With its ability to provide high-resolution, non-invasive images, MRI is crucial in evaluating soft tissues, including muscles, ligaments, tendons, cartilage, and bones. This research explores the role of MRI in diagnosing common musculoskeletal conditions such as osteoarthritis, sports injuries, and degenerative diseases. We review advancements in MRI techniques, including high-field imaging and contrast-enhanced MRI, and how these innovations have improved diagnostic accuracy. Furthermore, the paper discusses the clinical benefits of MRI in guiding treatment plans, monitoring disease progression, and enhancing post-injury rehabilitation. The growing use of MRI in musculoskeletal assessments highlights its importance in personalized healthcare, aiding in more targeted and effective therapies.